Japanese electronics multinationals and strategic trade policies - Belderbos, René A. (Clarendon Press, 1997)
Japanese electronics firms have grown into formidable competitors on world markets, but have only expanded seriously their manufacturing presence world-wide since 1985. This volume probes the difference of Japanese multinationals, and examines how the United States and Europe have responded to the Japanese challenge. Belderbos provides original insights into the determinants and effects of the internationalization of Japanese electronics firms and the relationship with trade policy measures in the United States and the European Union.